Curriculum Development for the Islamic Religious Education Study Program at Public Universities - Nida Shofiyah (Journal of Islamicate Studies, 2022)
Changing the shape of Higher Education from Colleges to Universities provides an opportunity for General Higher Education to open Islamic Studies study programs. This opportunity was captured by a Lecturer in Islamic Education (PAI) General Courses (MKU) at the Universitas Pendidikan Indonesia to open a program of Islamic Education, namely Islamic Science Education (IPAI). The initiative was taken because educational anxiety today uses Western theories and concepts that tend to be secular and value-free. This paper aims to determine the curriculum development carried out by the IPAI Study Program - Universitas Pendidikan Indonesia as one of the Islamic Education Study Programs at General Higher Education in Indonesia. Data collection techniques in this study were interviews, observation, and study documentation. Data analysis techniques using the model of Miles and Huberman with the stages of data reduction, data presentation, data interpretation, and conclusion. Test the validity of the data conducted by triangulating data sources, methods and theories, and member checks. The establishment of the IPAI Study Program aims to produce scientific knowledge, theorization and educational concepts that originate directly from the Al-Qur`?n and the Sunnah. The Islamic Science Education Study Program is different from the Islamic Education Study Program in Islamic Religious Higher Education because of its orientation which not only produces Islamic Education teachers but is a scientist in the field of Islamic education, entrepreneurs, and practitioners in non-formal and informal Islamic Education institutions.